2016
DOI: 10.1111/and.12703
|View full text |Cite
|
Sign up to set email alerts
|

Total antioxidant status and lipid peroxidation with and withoutin vitrozinc supplementation in infertile men

Abstract: The aim of this study was to assess the total antioxidant capacity (TAC) and malondialdehyde (MDA) level in infertile men with asthenozoospermia and asthenoteratozoospermia compared to fertile donors, and to examine the effect of zinc on sperm lipid peroxidation and antioxidant status in infertile and fertile men. Semen samples provided by infertile men (n = 38) and fertile donors (controls; n = 12) were exposed to 6 mmol/L of zinc for 2 hr at 37°C. After semen analysis, lipid peroxidation was detected by MDA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…It acts via a positive antioxidant action through glutathione peroxidase enzymes (Moslemi & Tavanbakhsh, ). Both vitamin E and zinc play a role in antioxidant balance regulation and are able to improve sperm concentration, percentage of progressively motile sperm and consequently pregnancy rate (Ajina, Sallem, Haouas, & Mehdi, ; Chen et al., ). Coenzyme Q10 levels show a significant correlation with sperm count and with sperm motility (Festa et al., ; Mancini et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…It acts via a positive antioxidant action through glutathione peroxidase enzymes (Moslemi & Tavanbakhsh, ). Both vitamin E and zinc play a role in antioxidant balance regulation and are able to improve sperm concentration, percentage of progressively motile sperm and consequently pregnancy rate (Ajina, Sallem, Haouas, & Mehdi, ; Chen et al., ). Coenzyme Q10 levels show a significant correlation with sperm count and with sperm motility (Festa et al., ; Mancini et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…However ROS, under physiological conditions, are important to many process can occur, such as events involving reproductive process, like sperm capacitation, hypermotility, cellular activation, interaction with zona pellucida and acrosome reaction (Banihani et al, ; Moretti et al, ; Satorre et al, ). Thereby, both oral and in vitro antioxidant supplementation have been reported as an attempt to reduce the damage caused by oxidative stress (Ajina, Sallem, Haouas, & Mehdi, ; Cyrus, Kabir, Goodarzi, & Moghimi, ; Ghafarizadeh, Vaezi, Shariatzadeh, & Malekirad, ; Ilić, Kolarević, Kocić, & Šmelcerović, ; Rafiee, Morowvat, & Rahimi‐Ghalati, ). In this study, the authors aimed to evaluate sperm function after semen processing by discontinuous gradient density supplemented with two different carnosine concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Such results might be unexpected because Zn is considered to possess antioxidant property, since it works as a co-factor of some antioxidant defense enzymes (Marreiro et al, 2017). However, Ajina et al (2017) reported that Zn provided to infertile men with asthenozoospermia and asthenoteratozoospermia did not prevent sperm lipid peroxidation or more recently, some authors (Lee, 2018;Marichali et al, 2016) described that an excess of Zn may cause oxidative stress evidenced by increased lipid peroxidation products (MDA) due to its pro-oxidant activity leading to cellular death.…”
Section: Antioxidant and Anti-inflammatory Activitiesmentioning
confidence: 99%